GAMBARAN PRESTASI BELAJAR MAHASISWA JURUSAN PENDIDIKAN FISIKA DALAM KAITANNYA DENGAN PEMINATAN PILIHAN DALAM PROSES PENERIMAAN MAHASISWA BARU - ., Kasmawati (Idaarah: Jurnal Manajemen Pendidikan, 2017)
The main problem in this research is how the description of student achievement in the Department of Physics Education in relation to the specialization of choice in the process of admission of new students. From the results of research shows that the picture of Physics Education student achievement that chose the Department of Physics Education as the first choice, is generally categorized as Cum Laude and Very Satisfactory or can be said good. Picture of student achievement of Physics Education Education who did not choose Education Department as first choice, from research data also good or in category Cum Laude and Very Satisfactory.